Electroencephalographic Measurement on Post-stroke Sensory Deficiency in Response to Non-painful Cold Stimulation - Huang, Yanhuan; Jiao, Jiao; Hu, Junyan; Hsing, Chihchia; Lai, Zhangqi; Yang, Yang; Li, Zengyong; Hu, Xiaoling (Frontiers in Aging Neuroscience, 2022)
Background: Reduced elementary somatosensation is common after stroke. However, measurement of elementary sensation is frequently overlooked in the traditional clinical assessments, and has not been evaluated objectively at the cortical level. This study designed a new configuration for the measurement of post-stroke elementary thermal sensation by non-painful cold stimulation (NPCS). The post-stroke cortical responses were then investigated during elementary NPCS on sensory deficiency via electroencephalography (EEG), when compared with unimpaired persons. Method: Twelve individuals with chronic stroke and fifteen unimpaired controls were recruited. A 64-channel EEG system was used to investigate the post-stroke cortical responses objectively during the NPCS. A subjective questionnaire of cold sensory intensity was also administered via a numeric visual analogue scale (VAS). Three water samples with different temperatures (i.e., 25oC, 10oC, and 0oC) were applied to the skin surface of the ventral forearm for 3 seconds via glass beaker, with a randomized sequence on either left or right forearms of a participant. EEG relative spectral power (RSP) and topography were used to evaluate the neural responses toward NPCS with respect to the independent factors of stimulation side and temperature. Results: For unimpaired controls, NPCS initiated significant RSP variations, mainly located in the theta band with the highest discriminative resolution on the different temperatures (P<0.001). For stroke participants, the distribution of significant RSP spread across all EEG frequency bands, and the temperature discrimination was lower than that observed in unimpaired participants (P<0.05). EEG topography showed that the NPCS could activate extensive and bilateral sensory cortical areas after stroke. Significant group differences on RSP intensities were obtained in each EEG band (P<0.05). Meanwhile, significant asymmetry in RSP was observed when NPCS was applied to different upper limbs in both unimpaired and stroke participants (P<0.05). No difference was found between the groups in the VAS ratings of the different temperatures (P>0.05). Conclusions: The post-stroke cortical responses during NPCS on sensory deficiency were characterized by wide distribution of representative RSP bands, lowered resolution toward different temperatures, and extensive activated sensory cortical areas.